"Unbreak My Heart": Clinical Implications for Working With Bereaved Couples. (July 2021) - Hall, Cadmona A.; Ungureanu, Ileana
Death and bereavement remain a cultural taboo that continues to impact helping professionals. The death of a child is a particularly difficult loss as it challenges expectations about the life cycle. Many clinicians find themselves unprepared and ill-equipped to appropriately intervene. Bereaved couples require knowledgeable and culturally competent support to facilitate positive and healthy outcomes. The aim of this article is to provide clinicians with a theoretical framework and clinical conceptualization to assess and intervene in the lives of bereaved couples.